Evaluasi Program Praktek Kerja Industri di Siswa Sekolah Menengah Kejuruan (SMK) - Supadi, Supadi (JTP - Jurnal Teknologi Pendidikan, 2017)
This study aims to describe the context, input, process, and product of industrial work practices program in Administrative Expertise Program of SMK BPS & K II Bekasi. This research is a program evaluation research using CIPP model. The methodology used is survey and descriptive method. The research was conducted at SMK BPS & K II Bekasi. The research informants were the head of prakerin, prakerin treasurer, supervising teacher, industry supervisor and students. Data were collected through observation, questionnaire, and interview. Based on data analysis found that the level of achievement of prakerin program on the context of program prakerin in Program Administration Expertise SMK BPS&K II Bekasi 85.16% with good category. The input variable of prakerin program in Administration Expertise Program of SMK BPS & K II Bekasi is 82,77% with good category. Variable process of prakerin program in Administration Expertise Program of SMK BPS & K II Bekasi is 85,03% with good category. Variable product of prakerin program in Administration Expertise Program of SMK BPS & K II Bekasi is indicated with excellent category with 96% passing rates of competency test.